Prehospital delay and time to reperfusion therapy in ST elevation myocardial infarction - George, Linsha (J Emerg Trauma Shock, 2017)
BACKGROUND: Despite efforts aimed at reducing the prehospital delay and treatment delay, a considerable proportion of patients with ST elevation myocardial infarction (STEMI) present late and receive the reperfusion therapy after unacceptably long time periods. This study aimed at finding out the patients' decision delay, prehospital delay, door-to-electrocardiography (ECG), door-to-needle, and door-to-primary percutaneous coronary intervention (PCI) times and their determinants among STEMI patients. MATERIALS AND METHODS: A cross-sectional study conducted among 96 patients with STEMI admitted in a tertiary care center in South India. The data were collected using interview of the patients and review of records. The distribution of the data was assessed using Kolmogorov–Smirnov test, and the comparisons of the patients' decision delay, prehospital delay, and time to start reperfusion therapy with the different variables were done using Mann–Whitney U-test or Kruskal–Wallis test based on the number of groups. RESULTS: The mean (standard deviation) and median (range) age of the participants were 55 (11) years and 57 (51) years, respectively. The median patients' decision delay, prehospital delay, door-to-ECG, door-to-needle, and door-to-primary PCI times were 75, 290, 12, 75, 110 min, respectively. Significant factors associated (P < 0.05) with patients' decision delay were alcoholism, symptom progression, and attempt at symptom relief measures at home. Prehospital delay was significantly associated (P < 0.05) with domicile, difficulty in arranging money, prior consultation at study center, place of symptom onset, symptom interpretation, and mode of transportation. CONCLUSIONS: The prehospital delay time among the South Indian population is still unacceptably high. Public education, improving the systems of prehospital care, and measures to improve the patient flow and management in the emergency department are essentially required. The time taken to take ECG and to initiate reperfusion therapy in this study points to scope for improvement to meet the American Heart Association recommended timings.